2019
DOI: 10.3390/molecules24112088
|View full text |Cite
|
Sign up to set email alerts
|

Homo- and Copolymerization of Ethylene with Norbornene Catalyzed by Vanadium(III) Phosphine Complexes

Abstract: Herein, we report the homo- and co-polymerization of ethylene (E) with norbornene (NB) catalyzed by vanadium(III) phosphine complexes of the type VCl3(PMenPh3-n)2 [n = 2 (1a), 1 (1b)] and VCl3(PR3)2 [R = phenyl (Ph, 1c), cyclohexyl (Cy, 1d), tert-butyl (tBu, 1e)]. In the presence of Et2AlCl and Cl3CCOOEt (ETA), 1a–1e exhibit good activities for the polymerization of ethylene, affording linear, semicrystalline PEs with a melting temperature of approximately 130 °C. Mainly alternating copolymers with high comono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…21 The recent resurgence of vanadium stems from the use of Schiff−base phenoxyimine−type ligands by Fujita at Mitsui. 13 Since then, a set of vanadium complexes supported by mono-and multi-dentate ligands, [22][23][24] including phenoxyimines, 25 aryloxides, 26 β−enaminoketonato, 27 diaminebis(phenolate), 28 bis(arylimo)acenaphthene, 29 phosphine, [30][31][32] oxazoline, 33 and N-heterocyclic carbenes 34 have been successfully developed. In this framework, we recently reported the synthesis of a set of phosphine adducts of (imido)V(IV) complexes, and we demonstrated their successful application as catalyst precursors for the copolymerization of ethylene with cyclic olefins.…”
Section: Introductionmentioning
confidence: 99%
“…21 The recent resurgence of vanadium stems from the use of Schiff−base phenoxyimine−type ligands by Fujita at Mitsui. 13 Since then, a set of vanadium complexes supported by mono-and multi-dentate ligands, [22][23][24] including phenoxyimines, 25 aryloxides, 26 β−enaminoketonato, 27 diaminebis(phenolate), 28 bis(arylimo)acenaphthene, 29 phosphine, [30][31][32] oxazoline, 33 and N-heterocyclic carbenes 34 have been successfully developed. In this framework, we recently reported the synthesis of a set of phosphine adducts of (imido)V(IV) complexes, and we demonstrated their successful application as catalyst precursors for the copolymerization of ethylene with cyclic olefins.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the relatively low cost and large variety of phosphines encourage the development of metal-phosphine complexes. The vanadium(III) (I-VII) and vanadium(IV) (VIII-X) catalysts with phosphine ligands used in the Et-NB copolymerization are complexes with monodentate and bidentate ligands [30,[52][53][54].…”
Section: Phosphine Ligandsmentioning
confidence: 99%
“…To prevent this, ethyl trichloroacetate (ETA) reactivator is often used. Another method of stabilizing the vanadium active center is applying ligands with electron-donating atoms, oxygen or nitrogen [ 14 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. In our previous works it was found that the vanadium metallocene and post-metallocene catalysts with oxazoline ligand activated by the traditional organoaluminium compound (AlEt 2 Cl) and ETA can be successfully used for COC synthesis [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%